Does a Consumer-Targeted Deprescribing Intervention Compromise Patient-Healthcare Provider Trust? - Yi Zhi Zhang; Justin P. Turner; Philippe Martin; Cara Tannenbaum (MDPI AG, 2018)
One in four community-dwelling older adults is prescribed an inappropriate medication. Educational interventions aimed at patients to reduce inappropriate medications may cause patients to question their prescriber’s judgment. The objective of this study was to determine whether a patient-focused deprescribing intervention compromised trust between older adults and their healthcare providers. An educational brochure was distributed to community-dwelling older adults by community pharmacists in order to trigger deprescribing conversations. At baseline and 6-months post-intervention, participants completed the Primary Care Assessment Survey, which measures patient trust in doctors and pharmacists. Changes in trust were ascertained post-intervention. Proportions with 95% confidence intervals (CI), and logistic regression were used to determine a shift in trust and associated predictors. 352 participants responded to the questionnaire at both time points. The majority of participants had no change or gained trust in their doctors for items related to the choice of medical care (78.5%, 95% CI = 74.2–82.8), communication transparency (75.4%, 95% CI = 70.7–79.8), and overall trust (81.9%, 95% CI = 77.9–86.0). Similar results were obtained for participants’ perceptions of their pharmacists, with trust remaining intact for items related to the choice of medical care (79.4%, 95% CI = 75.3–83.9), transparency in communicating (82.0%, 95% CI = 78.0–86.1), and overall trust (81.6%, 95% CI = 77.5–85.7). Neither age, sex nor the medication class targeted for deprescribing was associated with a loss of trust. Overall, the results indicate that patient-focused deprescribing interventions do not shift patients’ trust in their healthcare providers in a negative direction.